Muscle function, physical function, and gait in older women with and without knee osteoarthritis - Renata Wolf; Gleber Pereira; Fernanda de Mattos; Angélica Lodovico; Paulo Cesar Barauce Bento (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: To compare muscle function of knee extensors, gait parameters, and physical function in older women with and without knee osteoarthritis (KOA) and to associate these parameters to the KOA incidence in this population. Methods: Sixteen older women with KOA (66.9 ± 5.5 years; 74.9 ± 10.0 kg; 157.9 ± 0.9 cm; 30.2 ± 5.0 kg/m2) and fourteen healthy counterparts (control group: CG; 68.8 ± 5.8 years; 68.9 ± 10.5 kg; 158 ± 0.06 cm; 27.4 ± 4.0 kg/m2) participated in this study. Muscle function, physical function, and gait parameters were evaluated in both groups. The Western Ontario and McMaster Index (WOMAC) questionnaire was answered only by the KOA group. A correlation was performed to verify if KOA incidence was associated with muscle function, physical function, and gait parameters. Results: KOA group showed lower peak torque at 60°/s (30%; p = 0.003) and 180°/s (37%; p < 0.001), greater acceleration time at 60°/s (382%; p < 0.001), lower cadence (12.2%; p = 0.002), slower gait speed (19.5%; p < 0.001) and greater stride time (12.5%; p = 0.001) than CG group. However, there was no difference between groups in physical function (p < 0.0045). The KOA incidence presented a negative correlation with peak torque (rho = −0.602; p < 0.001), cadence (rho = −0.533; p = 0.002), gait speed (rho = −0.633; p < 0.001), stride length (rho = −0.517; p = 0.003) and a positive correlation with stride time (rho = 0.533; p = 0.002) and acceleration time (rho = 0.655; p < 0.001). Conclusion: Our findings suggest that knee osteoarthritis may impair the function of the knee extensors muscles and gait parameters. An association between the ability to produce force rapidly and gait speed with the KOA incidence in older women was also observed.